Human leptospirosis vaccines in China - Yinghua Xu; Qiang Ye (Taylor & Francis Group, 2018)
The present incidence of leptospirosis in China is significantly lower than past rates, although small localized outbreaks continue to occur in epidemic regions. Improvements in sanitation, as well as vaccination of high-risk populations, have played crucial roles in reducing the disease burden. Several types of human leptospirosis vaccines have been developed, including inactivated whole-cell, outer-envelope, and recombinant vaccines. Of these, only a multivalent inactivated leptospirosis vaccine is available in China, which was added to the Chinese Expanded Program on Immunization in 2007. However, this vaccine elicits serogroup-specific immunity, and serogroup epidemiology should continue to be monitored to enhance vaccine coverage and distribution. On the other hand, the efficiency of the inactivated vaccine should be further improved by optimizing the formulation, and by expanding the target population. More importantly, additional investments should be made to develop universal recombinant vaccines.